LIBRARY 2.0 TIDAK TERASA ADA DI SEKITAR KITA - Widyawan, Rosa (BACA: Jurnal Dokumentasi dan Informasi, 2010)
This essay reveals application of Web 2.0 tools in some Indonesia university, academic, and special libraries. It is an explorative preliminary study, and this literature based article is a starting effort to conduct a more comprehensive research in this subject. Fifteen library web pages are examined to identify their application of Web 2.0 tools. It finds out that some of them use such tool, but they seem not really aware the advantages of Web 2.0 for their libraries. This essay suggest that the implementation of Web 2.0 tools should be supported by decission makers.